Mengukur Efektivitas Interactive Control Systems: Studi Kasus pada Perusahaan Distributor Alat Kesehatan - Manurung, Cindy Theresia; Bachtiar, Emil (https://jurnal.binamandiri.ac.id/, 2023)
This study aims to evaluate the implementation of an interactive control system at PT. XYZ in the face of strategic uncertainty related to domestic component level (TKDN) policies. This evaluation was carried out due to the company's poor financial performance since the TKDN policy was issued. This is thought to have occurred due to the implementation of an interactive control system that was less effective in the company. The method used in this research is a case study, where data collection is carried out by means of semi-structured interviews, which are then analyzed using technical methods of deductive analysis, where the analysis process starts from theory to facts and data collected. The results showed that the application of an interactive control system at PT. XYZ was less effective. This is because the company was late in responding to the strategic uncertainty it faced in 2018. However, in 2021, the company will not repeat the same mistake and chooses to respond directly to the strategic uncertainty by choosing a control system.